Evolution of Human Memory B Cells From Childhood to Old Age - Ciocca, Michela; Zaffina, Salvatore; Fernandez Salinas, Ane; Bocci, Chiara; Palomba, Patrizia; Conti, Maria Giulia; Terreri, Sara; Frisullo, Giuseppe; Giorda, Ezio; Scarsella, Marco; Brugaletta, Rita; Vinci, Maria Rosaria; et al. (Frontiers in Immunology, 2021)
High quality medical assistance and preventive strategies, including pursuing a healthy lifestyle, result in a progressively growing percentage of older people. The population and workforce is aging in all countries of the world. It is widely recognized that older individuals show an increased susceptibility to infections and a reduced response to vaccination suggesting that the aged immune system is less able to react and consequently protect the organism. The SARS-CoV-2 pandemic is dramatically showing us that the organism reacts to novel pathogens in an age-dependent manner. The decline of the immune system observed in aging remains unclear. We aimed to understand the role of B cells. We analysed peripheral blood from children (4-18 years); young (23-60 years) and elderly (65-91 years) by flow cytometry. We also measured antibody secretion by ELISA following a T-independent stimulation. Here we show that the elderly have a significant reduction of CD27dull memory B cells, a population that bridges innate and adaptive immune functions. In older people, memory B cells are mostly high specialized antigen-selected CD27bright. Moreover, after in vitro stimulation with CpG, B cells from older individuals produced significantly less IgM and IgA antibodies compared to younger individuals. Aging is a complex process characterized by a functional decline in multiple physiological systems. The immune system of older people is well equipped to react to often encountered antigens but has a low ability to respond to new pathogens.